ASSESSMENT OF POTATO VARIETIES/HYBRIDS FOR FRENCH FRIES AND STORAGE BEHAVIOUR IN GUJARAT - Patel, R. N; Patel, N. H; Singh, S. V; Pandey, S K; Patel, J. M.; Patel, S. B. (Potato Journal, 2013)
Field trials were conducted at Deesa, Ladol and Anand during rabi seasons of 2002-03 to 200405 to evaluate the potato varieties/ hybrids for French fries making and longer shelf life. The results showed that high quality French fries can be prepared from heat tolerant hybrid HT/92-621, which produced highest French fries grade tuber yield with >21% tuber dry matter. Due to its excellent shelf life it can be stored in heap after harvest and appared suitable to supply raw material to French fries processing industries continuously up to four months without any appreciable storage losses.